COMPARISON OF OUTCOME BETWEEN OPEN HAEMORRHOIDECTOMY VERSUS TRANS-ANAL DOPPLER GUIDED HEMORRHOIDAL ARTERY LIGATION WITH RECTO-ANAL REPAIR IN 3RD AND 4TH DEGREE HAEMORRHOIDS - Irfan Saleem; Aqeela Shirazi; Shahid Farooq; Baseer Ullah; Lyba Ghayour; Subtain Haider; Habib ul Wahab Zia; Muhammad Sarmad Zafar (Journal of Ayub Medical College Abbottabad, 2023)
Background: Haemorrhoids are very common but their exact prevalence is not known as most of the people suffering from them do not seek medical or surgical advice. The literature states their prevalence to be about 39% and commonly affect people aged between 45-65 years of age. Objective of the study was to compare the outcomes of open haemorrhoidectomy Vs Trans anal Doppler ultrasound guided hemorrhoidal artery ligation with recto-anal repair in 3rd and 4th degree haemorrhoids. It was a Randomized control trial, conducted at the Department of Surgery, King Edward Medical University, Lahore; from October 2019 to March 2021. Methods: This was a randomized control trial study where the results of 70 patients of haemorrhoids including 3rd and 4th degree disease fulfilling the selection criteria, who underwent open haemorrhoidectomy (OH) and Doppler guided haemorrhoidal artery ligation with rectoanal repair (HAL RAR) procedure on elective and emergency operating lists, were analyzed with regards to post-operative pain, bleeding and hospital stay. Results: From our seventy patients the minimum age was 23 and maximum age limit was 55 years (mean: 35.09±7.47). There were 49 (70%) males and 21(30%) females. Mean post-op pain on day 7 for OH was 1.12±0.72 and for HAL RAR it was 1.06±0.52. Post-op bleeding (POB) occurred in 4(10%) patients in OH group and 2(6.66%) patients in HAL RAR group. Mean hospital stay for OH group was 2±0.45 and for HAL RAR it was 1.20±0.40, for POB, it was 1.9±0.30 in OH group and 1.86±0.34 in HAL-RAR group. Conclusion: There was no significant difference in mean post-op pain on day seven, and post-op bleeding, but there was significant difference in terms of mean hospital stay between the two groups.